LABELISASI HALAL ILLEGAL PADA PRAKTIK JUAL BELI PRODUK PANGAN DI LINGKUNGAN KAMPUS UIN BANDUNG SERTA RELEVANSI PANDANGAN HUKUM EKONOMI SYARIAH - Sari, Cunia Wulan; Nafisah, Didah Durrotun (Al-Muamalat: Jurnal Ekonomi Syariah, 2019)
ABSTRACT Halal labeling is very influencing consumers' interest in buying products because consumers believe in these products, in Islam it has also been explained that in the sale and purchase product must fulfill the requirements as the goods must be pure, useful, must belong to the seller, and the goods must be known. Regarding the guarantee of halal products, one of them is from the Law No. 33 of 2014. Where consumers have the right for the comfort, the secure in consuming goods or services. In this circumstance, the author found a case where the merchant or seller of the food products did not have a halal certificate and included the illegal-halal on their products. Based on the theoretical framework of buy and sell, there is a principle, one of the condition about the goods to be traded must be pure or not profane as explained in Islamic law. In this case, the seller of the food products that the authors have met they used illegal-halal labels and claimed that their food products were a hundred percent halal. This research This study uses a case-study method, which is expected to explain and reveal various problems related to the problems in this thesis, the data collected by the author is from the people or traders who run the businesses with illegal-halal labeled food products. From this research, it can be concluded that in the view of Islamic law this illegal-halal labeling is clearly very inconsistent, because the seller only sells or produces food products regardless of the halal listed in the composition.